The circles of life (4) Crowded house crowded field - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The circles of life (4) Crowded house crowded fieldDo not be alarmed, but there are Limits to Growth. Some say that the sky is the limit (and, yes, we know, women hold half the sky). As a species, we shall grow, from our current 6 billion to closer...